Effect of Sperm Ratio and Temperature on Fertilization and Early Larval Development of the Surf Clam Mesodesma donacium (Bivalvia:Mesodesmatidae) - Piera Vásquez-Calderón; Alejandro Abarca; L. René Durán; Doris Oliva (Animals, 2022)
The effect of sperm ratio on fertilization was evaluated in five sperm:oocytes treatments (10:1, 50:1, 100:1, 500:1 and 1000:1), the effect of temperature on embryonic and larval development in three temperature treatments (13 °C, 16 °C and 19 °C) was recorded and the duration of each stage, the growth rate and survival rate were registered. The oocytes were spherical (67.5 ± 4.2 μm) with a defined nucleus. Spermatozoa had a circular head (2 μm) and a fusiform flagellum (12 μm). The 500:1 sperm:oocytes treatment presented the lowest % of unfertilized oocytes, and lysis was observed in the 1000:1 treatment. An inverse relationship was observed between temperature and the duration of the stages of embryonic development. At 16 °C, veliger D larvae were observed at 41 h 45′ pf (88 ± 13.0 μm). Umbonate larvae were obtained at day 16 in the 13 °C culture and at day 10 in the 16 °C and 19 °C treatment (140 μm). On day 16 of culture, advanced umbonate larvae with a well-defined stomach (235 μm) were observed. The larval growth rate was higher in the 19 °C treatment (3.6 μm day−1) than the 13 °C and 16 °C treatment (2, 2.2 μm day−1). The mortality was higher in the 19 °C treatment (91%). These results are an initial contribution towards the culture of M. donacium as part of small-scale aquaculture in South America.